Екологічна освіта як умова формування культури здоров'я молодших школярів: вітчизнячний та зарубіжний досвід - Тетяна Завгородня (Pavlo Tychyna Uman State Pedagogical University, 2013)
У статті висвітлено проблеми поглиблення екологічних знань молодших школярі в Україні у контексті сучасних тенденцій розв'язання проблеми у зарубіжних країнах. Обґрунтовано взаємозалежність рівня екологічних знань і ефективності формування культури здоров'я в учнів молодших класів.  В статье раскрываются проблемы углубления экологических знаний младших школьников в Украине в контексте современных тенденций решения проблемы в зарубежных странах. Обоснована взаимообусловленность уровня экологических знаний и эффективности формирования культуры здоровья учащихся младших классов. The article deals with the problems of junior pupils' ecological education. The main attention is drawn to the tendencies in ecological education. First of all the emphasis is laid on linking ecological education to health care issues. Ukrainian elementary school curriculum has been analyzed in terms of ecological consciousness and ecological developing. The author states that these forms of classroom activities are organized on the regular basis. These activities are aimed at forming holistic vision as well as choosing healthy lifestyle. The other forms put into practice are: independent tasks, games, cooking competitions, out-of-school classes, discussions, etc. The author presents three main approaches to ecological education in Russia. The first one sees ways for improvement through developing new curriculum and syllabi. The second approach implies intensive use of ecology-related children's literature; the third one introduces more ecology issues into science textbooks. China stresses the importance of integrating ecology in all school subjects. In the UK ecology education is made up of three components: education about environment (knowledge), education for environment (values, behavior, treatment), and education in environment and through environment.